BASEL IV: APPROACH FOR DETERMINING THE CAPITAL CHARGES (Лучшие интеллектуальные исследования, 2024)
The final design of the new Basel IV: Standardized Measurement Approach (SMA) is less conservative than proposed in the consultation paper—however, the impact on capital requirements will, for some banks, still be severe.• Final approach• Capital impacts• Need for action• SummaryThe Basel Committee on Banking Supervision (BCBS) has finalized the Standardized Approach (SMA) for calculating the capital charges for operational risk.[1] Compared to the consultation paper, the approach has mainly stayed the same: the SMA consists of the two components Business Indicator Component (BIC) and Internal Loss Multiplier (ILM for short), which are multiplied by each other.[2]